Aportaciones de las lenguas prerromanas a la conformación del aragonés - Vázquez Obrador, Jesús (Caplletra. Revista Internacional de Filologia, 2002)
The paper focuses on the description of the pre-Roman component and its influence upon Aragonese. It casts light upon one of the factors proving most difficult to analyze, despite its importance for the description of Aragonese corn pare d to other neighbouring Romance varieties. The author reviews the various pre-Rom an linguistic substrata in North Aragon and the traces they left in the pronunciation, morphology and, more specifically, on lexis and toponymy.